Development of Interactive Multimedia in Citizenship Learning Class XI of SMK Professor Muhammad Zein Foundation, Padang Pariaman Regency - Hidayati Hidayati; Abna Hidayati (International Journal of Educational Dynamics, 2022)
This Research and Development aims to reveal 1) How is the interactive multimedia development process in Civics learning for Class XI SMK Yayasan Professor Muhammad Zein valid; and 2) How is an interactive multimedia practice in learning Citizenship Class XI SMK Yayasan Professor Muhammad Zein. This interactive multimedia development uses the Interactive Multimedia (IMM) Development model developed by Rob Philips (1997) which consists of five steps, namely Analysis, Design, Develop, evaluation, and implementation. Validity was tested from 3 aspects, namely media, material, and language aspects. Practicality was tested from the teacher's response and student response. While the effect was seen from the learning outcomes and student learning activities. The results of the average product validity scored 83.95% in the very valid category, the average student response practicality was 84.81% in the very practical category. The average practicality of teachers is 79.33% in the Practical category. Based on the data above, it can be concluded that the interactive multimedia of civics learning for class XI SMK Yayasan Professor Muhammad Zein is declared valid, practical, and effective to use in the learning process.